2008
DOI: 10.1158/1055-9965.epi-07-2621
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Anti-inflammatory and Antihistamine Medication Use and Adult Glioma Risk

Abstract: A personal history of asthma or allergy has been associated with a reduced risk for adult malignant gliomas. Recent reports on the use of nonsteroidal antiinflammatory drugs (NSAID) and the presence of risk alleles in asthma susceptibility genes showed similar inverse associations. To further explore the relationship between immune mediators and gliomas, we examined the use of NSAID and antihistamines, history of asthma or allergy, and infection in 325 glioma cases and 600 frequency-matched controls from the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 29 publications
3
77
1
2
Order By: Relevance
“…The influence of antihistaminic medication against allergies has been investigated in a large study showing also an inverse association with glioma. [13], however, Scheurer et al reported conflicting results [27]. In summary, recent studies on different polymorphisms and immunoglobulin E serum levels continued to show that further investigations on this topic are necessary to clarify the role of modulation of the immune system in the protection or promotion of glioma [1, 3-5, 8, 9, 13, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of antihistaminic medication against allergies has been investigated in a large study showing also an inverse association with glioma. [13], however, Scheurer et al reported conflicting results [27]. In summary, recent studies on different polymorphisms and immunoglobulin E serum levels continued to show that further investigations on this topic are necessary to clarify the role of modulation of the immune system in the protection or promotion of glioma [1, 3-5, 8, 9, 13, 28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…The findings were strongest for aspirin and ibuprofen. Another case-control study found a 33% lower risk for GBM in those reporting a regular use of NSAID (117). The authors failed in showing which NSAID had this effect.…”
Section: Allergies Atopic Conditions Infections Other Disease Medmentioning
confidence: 98%
“…Another study with 325 glioma cases and 600 frequency-matched controls in the metropolitan area of Houston (2001–2006) indicated that the regular use of NSAIDs was associated with a 33% reduction in the risk for glioma [81]. A case-control study on 517 cases and 400 population controls recruited at Columbia University Medical Center and the University of California, San Francisco from 2007 to 2010 was initiated to study the relation between NSAID use and the incidence of GBM.…”
Section: Human Studiesmentioning
confidence: 99%